The role of Salmon DNA in Skin Regeneration and Anti-Aging - Camilia, Anita; AP, Gadila; Dwiputri, Maliya Finda; Arief, Skolastika Faustina Ivana; Setyadi, Yudha Putra (SAFE-Network, 2025)
Salmon DNA, particularly its polydeoxyribonucleotide (PDRN) content, has attracted attention in dermatology due to its potential in skin regeneration and anti-aging applications. This review aims to summarize various research findings on the effectiveness of PDRN. The study was conducted through a literature review of articles published between 2016 and 2023. Findings indicate that PDRN works by activating adenosine A2a receptors, stimulating angiogenesis, cell proliferation, and reducing inflammation. Its combination with vitamin C and niacinamide enhances antioxidant effects and helps preserve the extracellular matrix. Furthermore, the use of long-chain polynucleotide fillers has been shown to significantly improve pore size, skin texture, wrinkles, and sagging, with minimal side effects. In conclusion, PDRN from salmon DNA is a promising bioactive agent for skin rejuvenation, wound healing, and anti-aging therapy in modern dermatological practice.